CONDUCTANCE OF SODIUM DODECYLSULFATE IN PRESENCE AND ABSENCE OF Na2SO4 AND ZnSO4 IN AQUEOUS MEDIA AT ROOM TEMPERATURE - Bhattarai, Ajaya; Shah, S K; Limbu, Kuber (Scientific World, 2015)
Conductance measurement of sodium dodecylsulfate in the presence and in the absence of Na2SO4 and ZnSO4 in aqueous media was done. The results showed sharp increase in conductance with increase in concentration of sodium dodecylsulfate. Also, the conductance increases with addition of salts. The conductance of sodium dodecylsulfate is found more in the presence of Na2SO4 than ZnSO4 in aqueous media. In the presence of salts, the critical micelle concentration (cmc) value decreases which are explained on the basis of the nature and ion size of the added ion. The graph of conductance versus concentration is used in determining the critical micelle concentration (cmc). Scientific World, Vol. 12, No. 12, September 2014, page 41-43